Bank Ratings and Lending Supply: Evidence from Sovereign Downgrades - Adelino, Manuel; Ferreira, Miguel A. (Review of Financial Studies, 2016)
We study the causal effect of bank credit rating downgrades on the supply of bank lending. The identification strategy exploits the asymmetric impact of sovereign downgrades on the ratings of banks at the sovereign bound relative to banks that are not at the bound as a result of rating agencies' sovereign ceiling policies. This asymmetric effect leads to greater reductions in ratings-sensitive funding and lending of banks at the bound relative to other banks. Results for foreign borrowers and within lender-borrower relationships confirm that credit demand does not explain our findings.